2017
DOI: 10.5737/23688076211223
|View full text |Cite
|
Sign up to set email alerts
|

Dépistage systématique de la détresse : portraits et regards croisés sur les perceptions des différents acteurs, perspectives cliniques et de recherche—Partie 1

Abstract: Cet article présente les résultats ayant trait à la première phase d'une étude à devis mixte séquentiel exploratoire (Creswell et Plano Clarke, 2007). Cette recherche a été rendue possible grâce au soutien financier de l'Association canadienne des infirmières en oncologie et de la Fondation de l'hôpital Maisonneuve-Rosemont, fonds administré par le Centre d'excellence en soins infirmiers de cette installation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 27 publications
1
2
1
2
Order By: Relevance
“…Our results are close from those of Tremblay and al [12] who reported the emotional categories at the first rank, after the physical category with the respective prevalence of 74.6% and 64%. About the spiritual category, this one was in the last position contrarily in our study where it was in the 3 rd rank; this could be explained in fact that all our patients had religious belief (96%).…”
Section: Distress In Oncologysupporting
confidence: 90%
See 2 more Smart Citations
“…Our results are close from those of Tremblay and al [12] who reported the emotional categories at the first rank, after the physical category with the respective prevalence of 74.6% and 64%. About the spiritual category, this one was in the last position contrarily in our study where it was in the 3 rd rank; this could be explained in fact that all our patients had religious belief (96%).…”
Section: Distress In Oncologysupporting
confidence: 90%
“…However, the prevalence in our study was upper in comparison to other studies of some authors just like Tremblay and al [12], Méry and al [2] with Dolbeault [5] who reported prevalence respectively in order of: 33.9%; 41% and 51.3%. Furthermore, our results were close from those of Howell and al [1] who reported a prevalence of 70%.…”
Section: Distress In Oncologycontrasting
confidence: 70%
See 1 more Smart Citation
“…ans la première phase de notre étude portant sur le dépis-tage de la détresse auprès de personnes atteintes de cancers du sein et hématologiques, phase qui constitue le sujet de la partie 1 de cet article (Tremblay et al, 2017, nous avons brossé les portraits de la détresse de ces deux groupes de participants atteints de cancer. Nous avons ainsi mis en évi-dence que bien que près de 34 % (33,9 %) de notre échantillon (N=532 participants) atteignent le score clinique de 5 et plus sur le thermomètre de la détresse (TD), un faible pourcentage d'entre eux (22,7 %) indique qu'ils souhaitent recevoir de l'aide pour les problèmes relevés lors du dépistage.…”
unclassified
“…Ces résultats peuvent tout autant indiquer la capacité de résilience de la clientèle atteinte de cancer tout comme les bénéfices des interventions de soutien et d'enseignement principalement réalisées par les infirmières et qui sont souvent peu documentées (De Marinis, et al, 2010;Tremblay et al, 2017).…”
unclassified